2013
DOI: 10.1063/1.4820825
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of nanostructuration from the heat capacities of the 1,3-dialkylimidazolium bis(trifluoromethylsulfonyl)imide ionic liquid series

Abstract: In the present work, the heat capacities at T = 298.15 K of 1,3-dialkylimidazolium bis(trifluoromethylsulfonyl)imide, [C N/2 C N/2 im][NTf 2 ], were measured, for the first time, using a high-precision heat capacity drop calorimeter, with an uncertainty of less than 0.15%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
25
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 29 publications
6
25
1
Order By: Relevance
“…The obtained stationary value of the glass transition temperature after the CAS can be associated with the unchangeable polar network grid type above the CAS, which seems to govern the relative stability between the glassya nd liquid states. This observation is in agreement with the structuration model derived from other experimental [22] and computational data, [23,24] which have shown that for both IL series at rend shift occurred at n = 6, the so-called criticala lkyl size (CAS), [11,25,26] due to an intensification of the nanostructuration in the liquid phase.…”
Section: Resultssupporting
confidence: 91%
“…The obtained stationary value of the glass transition temperature after the CAS can be associated with the unchangeable polar network grid type above the CAS, which seems to govern the relative stability between the glassya nd liquid states. This observation is in agreement with the structuration model derived from other experimental [22] and computational data, [23,24] which have shown that for both IL series at rend shift occurred at n = 6, the so-called criticala lkyl size (CAS), [11,25,26] due to an intensification of the nanostructuration in the liquid phase.…”
Section: Resultssupporting
confidence: 91%
“…Moreover, this macroscopic segregation behaviour has been shown to be a major feature in the ionic liquid bulk phase and as reflected in the thermophysical properties of ILs. [66][67][68][69][70][71][72][73] Similar trend shifts were observed in the IL viscosity, [66][67] surface tension, 68 vapour pressure, 69,70 heat capacity, 71 among others. 72,73 It is, however, thought-provoking to highlight that different trends on the IL acidity with increasing alkyl chain length have also been reported.…”
Section: Experimental Kamlet-taft Solvatochromic Parameterssupporting
confidence: 71%
“…They report on water solubility in a series of asymmetric and symmetric [CnCxim][NTf2] ILs (where n is up to 21 and x = 1 or n), extending their study of symmetric cations [36][37][38]. In order to analyse their solubility data, Density Functional theory calculations were also performed.…”
Section: [Saielli]mentioning
confidence: 99%
“…Since the appearance of the first experimental [4] and computational [2,3] proposals for such an organization, numerous studies provided more and more compelling evidences of this specific architecture. Several aspects have been explored in the last few years, including the role of alkyl chain length [5,9,[12][13][14][15][16][25][26][27][28][29][30], charged moieties chemical nature [5,15,16], polarity of the tail [12,20,21,[31][32][33], symmetry of the cation [34][35][36][37][38], effect of temperature [14,23,39] etc. It is stated that there is a strong correlation between structural complexity and performances of ILs.…”
mentioning
confidence: 99%